Alumina nanofiber aerogel and preparation method and application thereof
Patent Information
- Application Number
- CN202611110633.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-30
AI Technical Summary
然而,该方法所制备的气凝胶柔韧性仍显不足,氧化铝纳米线在外力作用下易断裂,且助剂的添加可能引入杂质,影响材料纯度及高温稳定性
本申请提出一种氧化铝纳米纤维气凝胶的制备方法,通过精巧的物料配比,并将形状记忆4D打印、静电纺丝与溶胶-凝胶化学相结合,实现了结构可定制、形状可编程的高性能氧化铝纳米纤维气凝胶的制备。具体的,以聚乳酸作为形状记忆功能组分,硝酸铝与异丙醇铝作为双铝源,聚乙烯吡咯烷酮作为纺丝成型助剂,乙醇为共同溶剂,构建具有可纺性与形状记忆特性的4D打印纺丝液。采用静电纺丝直写技术,实现氧化铝纳米纤维气凝胶前驱体的精确三维堆积,获得具有复杂宏观结构的凝胶前驱体;再通过干燥、模具定型与热处理,制备了具有定制复杂三维结构的4D氧化铝纳米纤维气凝胶。
Smart Images

Figure CN123003266A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of aerogel technology, and in particular to an alumina nanofiber aerogel, its preparation method, and its application. Background Technology
[0002] Alumina aerogel is a typical porous ceramic material that has shown significant application potential in aerospace, energy and chemical industries, and environmental remediation due to its low density, high specific surface area, excellent chemical stability and high temperature resistance.
[0003] However, alumina aerogels prepared using traditional methods generally suffer from poor mechanical properties, high brittleness, complex processes, and high costs, severely restricting their practical applications and functional development. To improve their mechanical properties, various improvement approaches have been proposed. For example, one method involves preparing alumina nanorods, combining gelation, aging, and supercritical drying processes, and then preparing nanorod aerogels through high-temperature pyrolysis. However, the aerogels obtained by this method have high density and low specific surface area, resulting in unsatisfactory thermal insulation performance, and the material brittleness problem remains unresolved. Another study uses high aspect ratio alumina nanowires for three-dimensional overlapping and introduces silica sol and boric acid as sintering aids to prepare aerogels. However, the aerogels prepared by this method still lack flexibility; the alumina nanowires are prone to breakage under external force, and the addition of aids may introduce impurities, affecting material purity and high-temperature stability.
[0004] Therefore, developing an alumina aerogel material that combines low density, high flexibility, and excellent thermal insulation properties is of great significance for breaking through existing technological bottlenecks and expanding its application in high-tech fields. Summary of the Invention
[0005] The main objective of this application is to provide an alumina nanofiber aerogel, its preparation method, and its application. The technical problem to be solved is how to provide an alumina aerogel material that combines low density, high flexibility, and excellent thermal insulation properties, thus making it more suitable for practical use.
[0006] The objective of this application and the technical problem it solves are achieved through the following technical solution. A method for preparing alumina nanofiber aerogel according to this application includes the following steps: S1. Mix polylactic acid powder with ethanol and stir evenly to obtain a shape memory solution; S2. Dissolve aluminum nitrate and aluminum isopropoxide in ethanol to obtain aluminum sol; the mass ratio of aluminum nitrate, aluminum isopropoxide and ethanol is 1:2.45~2.55:50~100. S3. Add polyvinylpyrrolidone to ethanol and stir until homogeneous to prepare an adhesive; S4. Mix the aforementioned binder with the aforementioned aluminum sol and stir until homogeneous to obtain a spinning solution; mix the aforementioned shape memory solution with the aforementioned spinning solution to obtain a 4D printing spinning solution; S5. Add the aforementioned 4D printing spinning solution into the syringe of the electrospinning equipment, set the programming graphics and path, and print to obtain the alumina nanofiber aerogel precursor. S6. After drying the aforementioned alumina nanofiber aerogel precursor, place it in a mold and keep it at 70~100℃ for 1~2 hours. After cooling to room temperature, open the mold to obtain alumina nanofiber aerogel.
[0007] The purpose of this application and the technical problems to be solved can also be further achieved by the following technical measures.
[0008] Preferably, in the aforementioned method for preparing alumina nanofiber aerogel, in step S1, the mass ratio of polylactic acid powder to ethanol is 1:2~5.
[0009] Preferably, in the aforementioned method for preparing alumina nanofiber aerogel, the stirring method in step S1 is to stir at 30℃~70℃ for 0.5~2h.
[0010] Preferably, in the aforementioned method for preparing alumina nanofiber aerogel, in step S2, aluminum nitrate is added to ethanol and stirred for 0.5 to 2 hours, then aluminum isopropoxide is added and stirred for 0.5 to 2 hours to prepare the aforementioned aluminum sol.
[0011] Preferably, in the aforementioned method for preparing alumina nanofiber aerogel, in step S3, the mass of the aforementioned binder is 100%, and the mass of polyvinylpyrrolidone is 3% to 10%.
[0012] Preferably, in the aforementioned method for preparing alumina nanofiber aerogel, in step S4, the mass of the aforementioned spinning solution is 100%, and the mass of the aforementioned binder is 30% to 70%.
[0013] Preferably, in the aforementioned method for preparing alumina nanofiber aerogel, in step S4, the mass of the aforementioned 4D printing spinning solution is 100%, and the mass of the aforementioned shape memory solution is 10% to 90%.
[0014] Preferably, in the aforementioned method for preparing alumina nanofiber aerogel, during electrospinning in step S5, the voltage is 10~30KV, the injection speed is 0.01~0.1mm / min, and the spinning distance increases at a rate of 1~10mm / h.
[0015] The purpose of this application and the solution to its technical problem are also achieved by the following technical solution. An alumina nanofiber aerogel according to this application is prepared by any of the aforementioned preparation methods, and the aforementioned alumina nanofiber aerogel recovers to the molded shape at 70~100℃.
[0016] The purpose of this application and the solution to its technical problems are also achieved by the following technical solutions. This application proposes the application of the aforementioned alumina nanofiber aerogel in the aerospace field.
[0017] By employing the above technical solution, the alumina nanofiber aerogel, its preparation method, and its application, as described in this application, have at least the following advantages: This application proposes a method for preparing alumina nanofiber aerogels. Through precise material formulation and the combination of shape memory 4D printing, electrospinning, and sol-gel chemistry, a high-performance alumina nanofiber aerogel with customizable structure and programmable shape is achieved. Specifically, polylactic acid is used as the shape memory functional component, aluminum nitrate and aluminum isopropoxide are used as dual aluminum sources, polyvinylpyrrolidone is used as a spinning aid, and ethanol is used as a co-solvent to construct a 4D printing spinning solution with spinnability and shape memory properties. Electrospinning direct-writing technology is used to achieve precise three-dimensional stacking of the alumina nanofiber aerogel precursor, obtaining a gel precursor with a complex macroscopic structure. Then, through drying, mold setting, and heat treatment, a 4D alumina nanofiber aerogel with a customized complex three-dimensional structure is prepared.
[0018] The core innovation of this method lies in the organic combination of shape memory 4D printing, electrospinning direct writing, and sol-gel conversion: shape memory polymers are used to achieve controllable deformation and fixation of materials under thermal stimulation; electrospinning direct writing enables the ordered arrangement and customized structure of fibers in three-dimensional space; and sol-gel chemical and thermal treatment is used to obtain an alumina nanofiber framework with ceramic intrinsic properties. The alumina nanofiber aerogel prepared in this way has a high-porosity interconnected network constructed from continuous alumina nanofibers, exhibiting excellent lightweight, low thermal conductivity, high elasticity and toughness, and unique shape memory and deformation programming capabilities.
[0019] These materials have broad application prospects in the aerospace field, and are particularly suitable for applications requiring lightweight, efficient thermal insulation, shape-adaptive or deformable structures, such as spacecraft thermal protection systems, flexible thermal insulation liner, and on-orbit deployable or variable-configuration thermal insulation components. They provide new ideas for the design of next-generation high-performance thermal insulation and structural-functional integrated materials.
[0020] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, the preferred embodiments of this application are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of alumina nanofiber aerogel in some embodiments of this application. Detailed Implementation
[0022] To further illustrate the technical means and effects adopted by this application to achieve its intended purpose, the following, in conjunction with the accompanying drawings and preferred embodiments, provides a detailed description of the specific implementation methods, structures, features, and effects of an alumina nanofiber aerogel, its preparation method, and its application based on this application. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable manner.
[0023] This application proposes a method for preparing alumina nanofiber aerogel, such as... Figure 1 As shown, the steps include: S1. Mix polylactic acid powder with ethanol and stir evenly to obtain a shape memory solution; S2. Dissolve aluminum nitrate and aluminum isopropoxide in ethanol to obtain aluminum sol; the mass ratio of aluminum nitrate, aluminum isopropoxide and ethanol is 1:2.45~2.55:50~100. S3. Add polyvinylpyrrolidone to ethanol and stir until homogeneous to prepare an adhesive; S4. Mix the aforementioned binder with the aforementioned aluminum sol and stir until homogeneous to obtain a spinning solution; mix the aforementioned shape memory solution with the aforementioned spinning solution to obtain a 4D printing spinning solution; S5. Add the aforementioned 4D printing spinning solution into the syringe of the electrospinning equipment, set the programming graphics and path, and print to obtain the alumina nanofiber aerogel precursor. S6. After drying the aforementioned alumina nanofiber aerogel precursor, place it in a mold and keep it at 70~100℃ for 1~2 hours. After cooling to room temperature, open the mold to obtain alumina nanofiber aerogel.
[0024] Specifically, in step S1, polylactic acid (PLA), as a shape memory polymer, is key to endowing the material with "4D" properties. PLA has thermally responsive shape memory function. When heated to above its glass transition temperature (60~70℃), the molecular chain segment mobility is enhanced, and the material can deform under external force (mold). After cooling, the deformation is "frozen" and fixed. When reheated to the trigger temperature, the material can return to the shape initially shaped by the mold. This allows the printed precursor structure to be controllably deformed and fixed according to the mold shape during subsequent heat treatment, realizing the customization of complex three-dimensional structures. Preferably, the mass ratio of polylactic acid powder to ethanol is controlled at 1:2~5. If there is too little ethanol, the PLA will not dissolve sufficiently, and the solution will be uneven; if there is too much ethanol, the PLA solution concentration will be too low, resulting in insufficient PLA content in the final 4D printing spinning solution, weakening the shape memory effect, and possibly failing to drive the aerogel precursor to deform sufficiently in the mold. Preferably, the polylactic acid powder and ethanol are mixed and stirred at 30℃~70℃ for 0.5~2h to obtain a shape memory solution.
[0025] In step S2, aluminum nitrate is added to ethanol and stirred for 0.5–2 h, followed by the addition of aluminum isopropoxide and stirring for another 0.5–2 h to obtain an aluminum sol. Aluminum nitrate, as an aluminum source, helps form alumina nuclei in the early stages of heat treatment, promoting the formation of the ceramic phase. The hydrolysis and polycondensation reaction of aluminum isopropoxide forms a continuous and uniform Al-O-Al network, which is fundamental for forming a high-quality alumina gel framework. The combination of aluminum nitrate and aluminum isopropoxide achieves a balance between low-temperature activity and gel network quality, ensuring the continuity and crystallinity of the final alumina fibers.
[0026] The mass ratio of aluminum nitrate, aluminum isopropoxide, and ethanol is controlled at 1:2.45~2.55:50~100; preferably, the mass ratio is controlled at 1:2.5:50~100. A molar ratio of aluminum isopropoxide to aluminum nitrate of approximately 1:1 is beneficial for forming a uniform alumina network; too little aluminum isopropoxide will result in an incomplete aluminum network structure; too much aluminum isopropoxide will cause excessively rapid gelation, leading to gelation during spinning and disrupting process continuity.
[0027] In step S3, polyvinylpyrrolidone (PVP) is a high molecular weight polymer with good fiber-forming and adhesive properties. Preferably, the mass percentage of PVP in the binder is 3% to 10%. If the PVP content is less than 3%, the adhesive properties are insufficient, and the fiber network formed by spinning is fragile and easily damaged during collection, transfer, or die pressing. If the PVP content is greater than 10%, the binder is too viscous and difficult to mix with aluminum sol.
[0028] Ethanol, as a general-purpose solvent, exhibits good solubility or dispersibility for PLA, aluminum nitrate, aluminum isopropoxide, and PVP, and is highly volatile with low toxicity. It ensures that all components can be uniformly mixed to form a homogeneous spinning solution, and rapidly evaporates during electrospinning and subsequent drying, promoting fiber solidification and the formation of a porous aerogel structure.
[0029] Preferably, in step S4, the binder accounts for 30% to 70% of the mass of the spinning solution, ensuring that the main body of the spinning solution has good spinnability while containing sufficient ceramic precursors. If the binder mass percentage is less than 30%, the fiber will be difficult to form; if the binder mass percentage is more than 70%, the ceramic yield will be reduced.
[0030] Preferably, in step S4, the shape memory solution accounts for 10% to 90% of the mass of the 4D printing spinning solution. The deformability and final ceramic yield of the material are programmed by adjusting the PLA content. A high shape memory solution content results in a strong shape memory effect and high deformability, but a relatively low final ceramic (alumina) yield; the aerogel is more flexible but its temperature resistance is slightly reduced. A low shape memory solution content results in a high ceramic yield, a more "ceramic" structure, and better high-temperature resistance, but a weaker shape memory effect and deformability. When the shape memory solution content is below 10%, the 4D deformation function is weak; when the shape memory solution content is above 90%, the structural strength of the precursor after heat treatment is lower.
[0031] Preferably, in step S5, during electrospinning, the voltage is 10~30KV, the injection speed is 0.01~0.1mm / min, and the spinning distance increases at a rate of 1~10mm / h. Controlling the voltage to 10~30KV allows the 4D printing spinning solution to form a stable Taylor cone and jet; if the voltage is too low, the jet will be unstable or even unable to start electrospinning; if the voltage is too high, the jet will be unstable, easily causing whipping and reducing deposition accuracy. Controlling the injection speed to 0.01~0.1mm / min, combined with the spinning distance increasing rate of 1~10mm / h, allows the nanofibers to be precisely deposited at specific locations, layer by layer, thereby constructing the preset three-dimensional structure; if the injection speed or spinning distance increase rate is too slow, the production efficiency will be low, and the needle may become clogged due to excessive solvent evaporation; if the injection speed is too fast, the solvent in the fiber will not evaporate sufficiently, easily leading to fiber adhesion and fusion, damaging the porous structure; if the spinning distance increase rate is too fast, it can easily affect the fineness of the deposition.
[0032] In step S6, the heat treatment temperature of the alumina nanofiber aerogel is 70~100℃, and the holding time is 1~2h. 70~100℃ is above the glass transition temperature of PLA but below its decomposition temperature. At this temperature, the PLA chain segment mobility is enhanced, the material softens, and under mold pressure, the aerogel precursor can be molded into the complex shape of the mold. After sufficient holding time, PLA undergoes stress relaxation and chain segment rearrangement. Upon cooling, the new shape is fixed. This process achieves permanent deformation fixation from the printed shape to the mold shape, which is the "programming" step of 4D printing. If the temperature is below 70℃ or the time is less than 1h, the PLA is not sufficiently softened, making deformation difficult; if the temperature is above 100℃, the PLA begins to soften and flow, leading to fiber structure fusion, decreased porosity, and even loss of the skeletal structure.
[0033] This application proposes an alumina nanofiber aerogel, such as Figure 1 As shown, the alumina nanofiber aerogel prepared by any of the aforementioned methods recovers to the molded shape at 70~100℃.
[0034] This application proposes the aforementioned application of alumina nanofiber aerogel in the aerospace field. Alumina nanofiber aerogel can be used as a lightweight ultra-insulating material in spacecraft thermal protection systems, or as a flexible load-bearing thermal insulation material in irregular parts; its shape memory properties can be used to design on-orbit self-deploying or deformable thermal insulation structures to meet the needs of spacecraft in different stages of launch (compact state) and on-orbit (deployed state).
[0035] The method for preparing alumina nanofiber aerogel proposed in this application uses polylactic acid as the shape memory polymer for 4D printing, aluminum nitrate and aluminum isopropoxide as raw materials, polyvinylpyrrolidone as a spinning aid, and ethanol as a solvent to prepare a spinning solution for 4D printing alumina nanofiber aerogel. A precursor for 4D printing alumina nanofiber aerogel is prepared through electrospinning. The 4D printing alumina nanofiber aerogel is then prepared through drying, mold pressing, and heat treatment. Through precise material ratios and process design, shape memory 4D printing, electrospinning, and sol-gel chemistry are combined to achieve precise deposition of three-dimensional structures. Secondary shape programming is performed using a thermal mold, successfully preparing 4D alumina nanofiber aerogels with customized complex three-dimensional structures. The alumina nanofiber aerogel prepared in this application consists of an interconnected network of alumina nanofibers, exhibiting high porosity, low density, and low thermal conductivity. It possesses excellent properties such as lightweight, thermal insulation, high elasticity, and high flexibility, as well as shape memory and customized deformation capabilities, showing promising application prospects in the aerospace field.
[0036] The present application will be further described below with reference to specific embodiments, but this should not be construed as a limitation on the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application are still within the scope of protection of the present application.
[0037] Unless otherwise specified, all materials and reagents mentioned below are commercially available products well known to those skilled in the art; unless otherwise specified, all methods described are methods known in the art. Unless otherwise defined, the technical or scientific terms used should have the ordinary meaning understood by one of ordinary skill in the art to which this application pertains.
[0038] Example 1 This embodiment provides an alumina nanofiber aerogel and its preparation method.
[0039] (1) Mix polylactic acid powder and ethanol at a mass ratio of 1:4 and stir magnetically at 50°C for 1 hour to obtain a shape memory solution.
[0040] (2) Add aluminum nitrate to ethanol and stir for 0.5 h, then add aluminum isopropoxide and stir for 1 h to obtain aluminum sol; the mass ratio of aluminum nitrate, aluminum isopropoxide and ethanol is 1:2.5:80.
[0041] (3) Add polyvinylpyrrolidone to ethanol and stir evenly to make an adhesive; the mass of the adhesive is 100% and the mass of polyvinylpyrrolidone is 4%.
[0042] (4) Mix the binder and aluminum sol at a mass ratio of 1:1 and stir until homogeneous to obtain the spinning solution. Mix the shape memory solution with the spinning solution to obtain the 4D printing spinning solution; the mass ratio of the shape memory solution to the spinning solution is 1:9.
[0043] (5) Add the 4D printing spinning solution into the syringe of the electrospinning equipment. Set the electrospinning parameters, including a voltage of 25KV, a injection speed of 0.01mm / min, and a spinning distance that increases with the printing thickness at a rate of 2mm / h. According to the preset shape, set the programming pattern and path, and print to obtain the alumina nanofiber aerogel precursor.
[0044] (6) The alumina nanofiber aerogel precursor was dried in a forced-air drying oven at 60°C for 24 hours, then placed in a mold and kept at 85°C in an oven for 1 hour. After cooling to room temperature, the mold was opened and the sample was removed to obtain alumina nanofiber aerogel. The alumina nanofiber aerogel recovered to the shape shaped by the mold at 85°C.
[0045] The alumina nanofiber aerogel was tested and found to have a thermal conductivity of 0.02 W / (m·K). It remained undeformed and undamaged after being folded 50 times at the same location, and its density at 85℃ was 0.12 g / cm³. 3 .
[0046] Example 2 The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of shape memory solution to spinning solution is 2:8.
[0047] The alumina nanofiber aerogel was tested and found to have a thermal conductivity of 0.025 W / (m·K). It remained undeformed and undamaged after being folded 100 times at the same location, and its density at 85℃ was 0.15 g / cm³. 3 .
[0048] Example 3 The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of shape memory solution to spinning solution is 3:7.
[0049] The alumina nanofiber aerogel was tested and found to have a thermal conductivity of 0.028 W / (m·K). It remained undeformed and undamaged after being folded 150 times at the same location, and its density at 85℃ was 0.18 g / cm³. 3 .
[0050] The technical features in the claims and / or specification of this application can be combined, and the combination is not limited to the combinations obtained through reference in the claims. Technical solutions obtained by combining the technical features in the claims and / or specification are also within the scope of protection of this application.
[0051] The above description is merely a preferred embodiment of this application and is not intended to limit this application in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of this application shall still fall within the scope of the technical solution of this application.
Claims
1. A method for preparing alumina nanofiber aerogel, characterized in that, The steps include: S1. Mix polylactic acid powder with ethanol and stir evenly to obtain a shape memory solution; S2. Dissolve aluminum nitrate and aluminum isopropoxide in ethanol to obtain aluminum sol; the mass ratio of aluminum nitrate, aluminum isopropoxide and ethanol is 1:2.45~2.55:50~100. S3. Add polyvinylpyrrolidone to ethanol and stir until homogeneous to prepare an adhesive; S4. Mix the binder with the aluminum sol and stir until homogeneous to obtain a spinning solution; mix the shape memory solution with the spinning solution to obtain a 4D printing spinning solution; S5. Add the 4D printing spinning solution into the syringe of the electrospinning equipment, set the programming graphics and path, and print to obtain the alumina nanofiber aerogel precursor. S6. After drying the alumina nanofiber aerogel precursor, place it in a mold and keep it at 70~100℃ for 1~2 hours. After cooling to room temperature, open the mold to obtain alumina nanofiber aerogel.
2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of polylactic acid powder to ethanol is 1:2~5.
3. The preparation method according to claim 1, characterized in that, In step S1, the specific method of stirring is to stir at 30℃~70℃ for 0.5~2h.
4. The preparation method according to claim 1, characterized in that, In step S2, aluminum nitrate is added to ethanol and stirred for 0.5 to 2 hours, then aluminum isopropoxide is added and stirred for 0.5 to 2 hours to prepare the aluminum sol.
5. The preparation method according to claim 1, characterized in that, In step S3, the mass of the adhesive is 100% and the mass of polyvinylpyrrolidone is 3% to 10%.
6. The preparation method according to claim 1, characterized in that, In step S4, the mass of the spinning solution is 100%, and the mass of the binder is 30% to 70%.
7. The preparation method according to claim 1, characterized in that, In step S4, the mass of the 4D printing spinning solution is 100%, and the mass of the shape memory solution is 10%~90%.
8. The preparation method according to claim 1, characterized in that, In step S5, during electrospinning, the voltage is 10~30KV, the injection speed is 0.01~0.1mm / min, and the spinning distance increases at a rate of 1~10mm / h.
9. An alumina nanofiber aerogel, characterized in that, The alumina nanofiber aerogel, prepared by any one of claims 1-8, recovers to the molded shape at 70-100°C.
10. The application of the alumina nanofiber aerogel according to claim 9 in the aerospace field.